Atributos urbanos e diferenciais regionais de salário no Brasil, 1991 e 2000 - Gustavo Geaquinto Fontes (2006)
The objective of the present work is to analyze the impact of urban economic attributes over the wage deferentials between Brazilian medium cities and metropolitan regions. It aims to introduce in the debate of wage determinants factors suposively impactant of local levels of productivity and of the regional structure of work demand. Thus, the intention was adding factors not just directly related to work supply, that is, to worker´s individual productive characteristics, like schooling and experience.This study uses micro data of 1991 and 2000 Demographic Census of Brazil and encompasses men workers living in urban areas and enployed in non agricultural activities. Estimation by two level hierarchical linear models enabled the inclusion of different level variables (individuals and urban centers) and the partition of total wage variance between workers and teritorial units. It was observed that a significant proportion of total individual wage dispersion is related to wage differentials among localities, signaling that regional characteristics affect the levels of individual wages. Firstly, it was identified the permanence of salary earnings disparities between workers with similar individual observable characteristics, but living in urban centers situated in different regions of the country. Besides the endowment of human capital, the employment sector of workers and some urban attributes, such as total population, industrial scale and urban density of modern producer services, also presented significant impact on wage determination. The results points out the importance of local economic factors, and not just the interurban differences on labor force qualification and experience, in the determination of the observed regional wage disparities.